The resistance of cork to decay by wood-destroying molds - DeBaun, Robert M; Nord, F F (Archives of Biochemistry and Biophysics, 1951)
A new method for the determination of the lignin in cork has been reported. This procedure gives values ca. 25–30%. It is based on the colorimetric estimation of the lignin released by autoclaving with alkali. Using this method it was shown that cork is highly resistant to decay by brown-rot wood-destroying molds. This is attributed to the protective action of the suberin or to the presence in the cork of substances toxic to the molds.
APS
Keywords: Cork; Lignin; molds; resistance